Epidermodysplasia Verruciformis in a Patient with a Renal Transplant: A Rare Case Report - Mahesh Mathur; Gautam Das; Swati Shah; Sunil Jaiswal; Srijana Maharjan; Ayasha Shrestha (European Medical Journal)
Acquired epidermodysplasia verruciformis is a rare condition that can occur in patients who are immunocompromised, particularly recipients of a renal transplant. In a patient who has had a renal transplant, acquired epidermodysplasia verruciformis has a greater propensity for developing non-melanoma skin cancer. It is critical to emphasise an early and accurate diagnosis, and regularly monitor this high-risk population.